Breed and non-genetic risk factors associated with the prevalence of subclinical mastitis in livestock systems of Arauca, Colombian Orinoquia. (2024)
Subclinical Mastitis (SCM) is caused by several factors associated with the interaction of the individual cow, cow management, and the environment. The aim of this study was to assess the breed and non-genetic risk factors on the prevalence of SCM in cows from the dual-purpose livestock system on the floodplain of Arauca, Colombian Orinoquia. Milk samples were taken from the individual mammary quarters of 481 cows representing 28 different farms where the electrical conductivity (EC) test applied. To determine the factors associated with SCM, a multiple logistic regression analysis was used. The response variable was the SCM presence (1), or absence (0) obtained with the EC test. Breed was included as a genetic risk factor, and as non- genetic risk factors: number of cows in production, daily milk production, lactation month, cow age, climatic period, body condition, and calving number. The factors that were significantly associated with the SCM presence were body condition, climatic period, and breed (p < 0.05). Odds ratio (OR) analysis of significant effects indicates that for each unit increase in body condition, the OR of having animals with SCM is reduced by 71%. In the dry period the OR of animals with SCM increases by 150% compared to the rainy period. Composite breeds reduce the OR of SCM animals by 73%, compared with Indicus-predominance animals. In this study, the occurrence of SCM in extensive management systems in Arauca, Colombian Orinoquia, is determined by the risk factors of breed, climatic period, and body condition.